Design and Analysis of Liquid Propellant Rocket Thruster - Montaser Saeed; Saad Adam; Mohammed Abu Elgasim (African Journal of Advanced Pure and Applied Sciences, 2024)
This paper explores the intricate design considerations of liquid propellant rocket thrusters, which are pivotal components in modern space exploration and satellite deployment. The study begins with an overview of liquid propulsion systems, highlighting their advantages such as high efficiency and the ability to throttle thrust. The design process incorporates various critical elements including the selection of propellants, the configuration of the combustion chamber, injector design, and cooling methods. In our study, the model was designed with dimensions by analytical and software. The propellant of the model has been selected. The model was drawn and analyzed by Ansys workbench software. The paper also addresses the integration of these components into a cohesive system, focusing on achieving a balance between performance, reliability, and manufacturability. Advanced computational simulations and empirical testing methodologies are employed to validate design choices and optimize the thruster’s performance. In conclusion, the design of liquid propellant rocket thrusters involves a complex interplay of material science, thermodynamics, and fluid dynamics. This paper provides a comprehensive framework for the design process, aiming to guide the development of efficient and reliable thrusters for future aerospace missions.